2020
DOI: 10.1007/s42452-020-3130-4
|View full text |Cite
|
Sign up to set email alerts
|

New insights into Pablo Picasso’s La Miséreuse accroupie (Barcelona, 1902) using X-ray fluorescence imaging and reflectance spectroscopies combined with micro-analyses of samples

Abstract: The existence of underlying structures in an x-radiograph of La Miséreuse accroupie (1902), a Blue Period painting in the collection of the Art Gallery of Ontario (AGO), prompted a comprehensive technical study to unpack how Picasso actually made this iconic work of art. A methodology was used in which 2D macroscopic data were collected in situ using fiber optics reflectance spectroscopy and macro-X-ray fluorescence mapping. It confirmed that Picasso painted over an earlier composition. It also revealed, betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Specifically, information about electronic transitions occurs mainly in the visible spectral range, and information about vibrational modes (combinations and overtones) in the short-wavelength infrared. During the last decades, research has shown that when RIS results are combined with other complementary non-invasive imaging techniques [ 5 , 6 , 7 ], a more complete understanding of the composition polychrome artworks such as manuscripts, wall paints [ 8 , 9 ] and, in particular, paintings [ 10 ] can be obtained. Furthermore, RIS has been proven to be useful in the study of Rembrandt’s paintings to help in the identification and mapping of pigments as well as to visualize changes in the painted composition [ 11 , 12 ] in spite of their often dark appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, information about electronic transitions occurs mainly in the visible spectral range, and information about vibrational modes (combinations and overtones) in the short-wavelength infrared. During the last decades, research has shown that when RIS results are combined with other complementary non-invasive imaging techniques [ 5 , 6 , 7 ], a more complete understanding of the composition polychrome artworks such as manuscripts, wall paints [ 8 , 9 ] and, in particular, paintings [ 10 ] can be obtained. Furthermore, RIS has been proven to be useful in the study of Rembrandt’s paintings to help in the identification and mapping of pigments as well as to visualize changes in the painted composition [ 11 , 12 ] in spite of their often dark appearance.…”
Section: Introductionmentioning
confidence: 99%
“…al. (31) which was removed from the tacking edge of Pablo Picasso's 1902 painting entitled La Miséreuse accroupie, painted during his Blue Period. From this cross-section, spectral image stacks were collected, and two illumination angles were selected and collapsed into separate RGB images: Figure 2A and 2B show the sample illuminated at β = 0 o and 180 o , respectively.…”
Section: Oi Microscope Design Approachmentioning
confidence: 99%
“…SEM-EDS indicated that this layer was aluminum-rich, previously inspiring the hypothesis that this layer contained an organic lake pigment. (31) Consequently, a reference sample containing a 180:1:1 w/w mixture of lead white : ultramarine : carmine naccarat was created. This reference matched the spectral features observed in the historical sample.…”
Section: Case Study Using a Cross-section From Picasso's La Miséreuse...mentioning
confidence: 99%
“…Nevertheless, MA-XRF only provides elemental composition and the electronic transitions associated with RIS typically produce a broad and sometimes unspeci c molecular response which means that additional spectroscopic methods are sometimes needed for an unambiguous pigment identi cation. For this study we also employed Raman and FTIR as well as scanning electron microscopy coupled to energy dispersive X-ray spectrometry (SEM-EDX) [16,21]. In the case of organic colorants, chromatographic techniques, such as high pressure liquid chromatography (HPLC) coupled to diode array detector (DAD) and/or mass spectrometry (MS) applied to micro-samples were integrated into the analytical protocol [22].…”
Section: Introductionmentioning
confidence: 99%